Quantitative aspects of phosphorus absorption and excretion in sheep - Bueno I.C.S.; Lopes J.B.; Sallam S.M.A.; Abdalla A.L.; Vitti D.M.S.S. (Nutritional and foraging ecology of sheep and goats, 2009)
The aim of the present study was to compile data from previous studies dealing with true digestibility of different phosphorous (P) sources for sheep. The database consisted of results from some experiments carried out at the Centre for Nuclear Energy in Agriculture (CENA/USP, Piracicaba, Brazil), using sheep fed different sources of P: dicalcium phosphate (n = 14); monoammonium phosphate (n = 12); triple superphosphate (n = 12); bone meal (n = 28); rock phosphates (n = 32). True absorption of phosphorus was determined by the isotopic dilution technique. All parameters (PING: ingested P; PABS: absorbed P; PFECTOT: total faecal P excretion; PFECENDO: endogenous faecal P; PFECNABS: dietary non absorbed P; and PRET: retained P) were normalized according to dry matter intake (DMI) and linear regressions between PING and the other parameters were tested. Excretion of P was affected by intake. Endogenous fraction of faecal P (PFECENDO) was not affected by PING. The present study showed that only 0.37 of ingested P was absorbed, i.e. about two thirds of ingested P were excreted via faeces, contributing to environmental pollution. Some sources of phosphorus can, in the long term, promote environmental damages due to their low availability for the animals.
12. Seminar on: Nutritional and Foraging Ecology of Sheep and Goats, 2007/10/11-13, Thessaloniki (Greece)